2015
DOI: 10.1055/s-0035-1554846
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Secondary to Household Air Pollution

Abstract: Approximately 3 billion people around the world cook and heat their homes using solid fuels in open fires and rudimentary stoves, resulting in household air pollution. Household air pollution secondary to indoor combustion of solid fuel is associated with multiple chronic obstructive pulmonary disease (COPD) outcomes. The exposure is associated with both chronic bronchitis and emphysema phenotypes of COPD as well as a distinct form of obstructive airway disease called bronchial anthracofibrosis. COPD from hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 86 publications
4
55
0
1
Order By: Relevance
“…Accordingly, the authors concluded that pulmonary hypertension was more common in the case than in the control group [33]. In a review article by Assad et al it was concluded that in COPD due to biomaterial smoke, in comparison to smoking-induced type, the bronchial involvement is more widespread, the emphysematous changes are less and the pulmonary hypertension is more severe [34]. We also reached a similar conclusion [35][36].…”
Section: Discussionsupporting
confidence: 83%
“…Accordingly, the authors concluded that pulmonary hypertension was more common in the case than in the control group [33]. In a review article by Assad et al it was concluded that in COPD due to biomaterial smoke, in comparison to smoking-induced type, the bronchial involvement is more widespread, the emphysematous changes are less and the pulmonary hypertension is more severe [34]. We also reached a similar conclusion [35][36].…”
Section: Discussionsupporting
confidence: 83%
“…However, indices of iron homeostasis were also associated with COPD in non-smokers. Etiologies of irreversible airway obstruction in non-smokers can include occupational exposures to particles (eg, miners, tunnel workers, and concrete workers and air pollution) 23,24. The basic mechanism of the biological effect of such particles is the same as that of cigarette smoke particles, that is, they also disrupt iron homeostasis resulting in an accumulation of iron with an oxidative stress and injury ensuing 25.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 There is growing evidence that indoor air pollution from biomass cooking and heating in poorly ventilated dwellings is an important risk factor for COPD. 7 The role of outdoor air pollution is unclear. Chronic and progressive dyspnoea is the cardinal symptom of COPD and a major cause of disability in these patients.…”
Section: Introductionmentioning
confidence: 99%